No evidence for cancer-related CD44 splice variants in primary and metastatic colorectal cancer - Givehchian, Mehdi; Wörner, S.; Sträter, Jörn; Zöller, M.; Heuschen, Udo; Heuschen, Gundi; Lehnert, Thomas; Herfarth, Christian; Knebel Doeberitz, Magnus von (European journal of cancer, 1998)
The expression of alternatively spliced CD44 adhesion molecules has been implicated in the pathogenesis and metastasis of colorectal cancer. Using a new set of primers for exon-specific reverse transcription-polymerase chain reaction (RT-PCR) we delineated the exact exon composition of CD44 mRNAs in normal colorectal mucosa, including isolated colonic crypts, in colorectal carcinomas and in their hepatic metastases. In addition, the surface expression of CD44 isoforms was analysed by immunohistochemistry. We identified by RT-PCR eight variant transcripts expressed in colorectal carcinomas and their metastases, but also constitutively in normal colorectal epithelia. In the normal colorectal epithelium, the surface expression of CD44 standard and variant molecules was restricted to proliferating cells at the bottom of the crypts. Despite expression of these transcripts in colorectal cancers and their metastases, monoclonal antibodies specific for standard or variant epitopes encoded by exons v5 and v6 stained only a few neoplastic lesions. These data point to a differentiation-specific CD44 expression and splicing pattern in proliferating colorectal epithelia. However, they do not support a cancer- or metastasis-specific CD44 splicing pattern. Instead, cell surface availability of CD44 epitopes was reduced rather than increased in primary tumours and particularly in liver metastases.
Online verfügbar: 2. September 1998
Gesehen am 27.10.2025